A estrutura De + SN como modificador do substantivo dose: uma análise funcional-cognitivista - Nolasco, Abraão Cleber Silva (2023)
Assuming that the noun dose meaning a “standard quantity of medicine, drink, etc.” requires further information for a specific sense to be effectively conveyed, thus falling into the category of syncategorematic words (CASTILHO, 2010), this study focuses on the structure De + SN functioning as a modifier of the noun dose. Twitter posts were observed, produced during the Covid-19 pandemic, in which the noun dose with the aforementioned meaning was sometimes accompanied by the De + SN structure, i.e., a term that encoded additional information, and sometimes not. Given the difficulty of distinguishing between Nominal Complement and Adnominal Adjunct, represented by De + SN when they are connected to a noun nucleus, and the lack of sufficient criteria for this distinction in previous works on this topic (IGNÁCIO, 2003), the Prepositional Phrase under study is classified as a modifier as terminology presented by Perini (2000; 2019). Accordingly, the main objective of this study is to analyze how the modifier De + SN of the noun dose is realized in tweets produced between October 2019 and October 2021, in order to examine how meanings emerge in language use. Classic Linguistic Functionalism, particularly studies on iconicity and informativity, combined with concepts from Cognitive Linguistics, particularly the notion of frames, served as theoretical foundations for investigating the functioning of this modifier in the collected tweets. Four modes of realization of the modifier were identified: linguistically realized modifier, partially realized modifier, anaphoric/cataphoric zero modifier, and inferred zero modifier. The explanation of these modes of realization of the modifier of the noun dose is based on the principles of iconicity and informativity, and the notion of frames is employed to understand the sense in the case of the inferred zero modifier. As this analytical endeavor deviates from a binary linguistic analysis, where the distinction between linguistic categories is categorical, it is believed that this study has the potential to contribute to linguistic research.